Self-Perception and Educational Experiences of Visually Impaired Students in Research Programs: An Interpretative Phenomenological Analysis - Dr. Tahira Batool Bokhari; Dr. Yaar Muhammad; Dr. Faisal Anis (Research Journal of Psychology, 2025)
This study aims to understand how visually impaired students in a Pakistani university make meaning of their identities and educational experiences. By using Interpretative Phenomenological Analysis (IPA), rich, descriptive data on five visually impaired doctoral candidates’ perceptions, coping strategies and challenges encountered within the academic environment was obtained using semi-structured interviews. The data analysis yielded the following three superordinate themes: (1) negotiating an academic identity in world of sight, (2) managing institutional barriers and support systems, and (3) developing resilience and adaptive strategies. Participants were found to be unable to remain stable or unchanging in relation to the educational institutions to which they are attached. Rather, a complex between personal agency, social interactions, and institutional factors occurs, in which participants actively reconstruct their academic identities. The study concludes that more inclusive educational policies, adaptive technologies, and support services are required in higher education institutions. This paper contributes to the limited literature on visually impaired students in the research degree programs, particularly in the Pakistani context, and informs on how practices of higher education can be inclusive to all.